2014
DOI: 10.1099/vir.0.060889-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel flavivirus in the soybean cyst nematode

Abstract: Heterodera glycines, the soybean cyst nematode (SCN), is a subterranean root pathogen that causes the most damaging disease of soybean in the USA. A novel nematode virus genome, soybean cyst nematode virus 5 (SbCNV-5), was identified in RNA sequencing data from SCN eggs and second-stage juveniles. The SbCNV-5 RNA-dependent RNA polymerase and RNA helicase domains had homology to pestiviruses in the family Flaviviridae, suggesting that SbCNV-5 is a positive-polarity ssRNA virus. SbCNV-5 RNA was present in all ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 48 publications
(62 reference statements)
1
41
0
1
Order By: Relevance
“…2C). BLAST searches indicated that AFV has 20% amino acid identity to gentian Kobu-sho-associated virus (GKaV), a recently identified flavi-like virus originally thought to be a dsRNA virus (Table 2) (35, 57, 58). Similarly to GKaV and other newly identified flaviviruses, the 20.4-kb AFV-1 genome is longer than the typical length of previously characterized members of the Flaviviridae (35).…”
Section: Resultsmentioning
confidence: 99%
“…2C). BLAST searches indicated that AFV has 20% amino acid identity to gentian Kobu-sho-associated virus (GKaV), a recently identified flavi-like virus originally thought to be a dsRNA virus (Table 2) (35, 57, 58). Similarly to GKaV and other newly identified flaviviruses, the 20.4-kb AFV-1 genome is longer than the typical length of previously characterized members of the Flaviviridae (35).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, virome analysis of bats has provided indications for novel pestiviruses in these mammals , but the significance of these findings still has to be supported by further analyses. A recent publication reports on a novel flavivirus with homology to pestiviruses in a soybean cyst nematode (Bekal et al, 2014).…”
Section: General Properties Hosts and Transmissionmentioning
confidence: 99%
“…Despite possessing exceptionally long genomes (23 and 19 kb, respectively), these two viruses have the basic flavi-like genome/proteome structure, as well as sequence homology in the serine protease, helicase, and RNAdependent RNA polymerase (RdRp) domains of the polyprotein. Although GKaV was reported to be a double-stranded RNA (dsRNA) virus (14), the RNA digestion experiment was performed on crude plant extracts where the dsRNA is more likely to be the replication complex rather than the genome itself (15). More remarkable was the recent demonstration that Jingmen tick virus (JMTV) and Toxocara canis larva agent (TCLA) are clearly related to flaviviruses but possess a very different genomic plan comprising four distinct segments (11), in turn raising questions about the evolutionary link between segmented and unsegmented genomes.…”
mentioning
confidence: 99%